Mental Health Literacy among Family Caregivers of Schizophrenia Patients - Mohd Suhaimi, Mohamad; Zabidah, Putit; Fauziah, Ibrahim; Norul, Sar (Canadian Center of Science and Education, 2012)
The benefits of public knowledge towards physical health are widely accepted but the area of mental health literacy remains undervalued and relatively neglected. The study aimed to identify caregivers’ mental health literacy in Malaysia. There were 154 family caregivers participated in the face-to-face semi-structured interview regarding their personal caring experiences. This study found that majority of the caregivers was women aged less than 60 years. Most of the caregivers have some understanding about their relatives’ mental illness. More than half of the participants found that the doctors were considered as their primary source of information about mental health. Consistent with previous literature in Malaysia, most of the caregivers used religious and traditional coping mechanism in their help-seeking processes. Each ethnic group had their own strong cultural beliefs about mental illness. The implications for mental health services are that many of the caregivers need help to educate their family members about mental illness. While this study emphasized on the family members who should be targeted to improve mental health literacy it also become significant to the public to reduce stigma towards the person with mental illness and their family.